STAKEHOLDER INVOLVEMENT IN THE HEALTH TECHNOLOGY ASSESSMENT PROCESS IN LATIN AMERICA. (11th June 2018) - Pichon-Riviere, Andres; Soto, Natalie; Augustovski, Federico; Sampietro-Colom, Laura
Abstract : Objectives: Latin American countries are taking important steps to expand and strengthen universal health coverage, and health technology assessment (HTA) has an increasingly prominent role in this process. Participation of all relevant stakeholders has become a priority in this effort. Key issues in this area were discussed during the 2017 Latin American Health Technology Assessment International (HTAi) Policy Forum. Methods: The Forum included forty-one participants from Latin American HTA agencies; public, social security, and private insurance sectors; and the pharmaceutical and medical device industry. A background paper and presentations by invited experts and Forum members supported discussions. This study presents a summary of these discussions. Results: Stakeholder involvement in HTA remains inconsistently implemented in the region and few countries have established formal processes. Participants agreed that stakeholder involvement is key to improve the HTA process, but the form and timing of such improvements must be adapted to local contexts. The legitimization of both HTA and decision-making processes was identified as one of the main reasons to promote stakeholder involvement; but to be successful, the entire system of assessment and decision making must be properly staffed and organized, and certain basic conditions must be met, including transparency in the HTA process and a clear link between HTA and decision making. Conclusions: Participants suggested a need for establishing clear rules of participation in HTA that would protect HTA producers and decision makers from potentially distorting external influences. Such rules and mechanisms could help foster trust and credibility among stakeholders, supporting actual involvement in HTA processes.